Auctions with Resale Markets: An Exploratory Model of Treasury Bill Markets - Bukhchandani, Sushil; Huang, Chi-fu (Review of Financial Studies, 1989)
This article develops a model of competitive bidding with a resale market. The primary market is modeled as a common-value auction, in which bidders participate for the purpose of resale. After the auction the winning bidders sell the objects in a secondary market, and the buyers in the secondary market receive information about the bids submitted in the auction. The effect of this information linkage between the primary auction and the secondary market on bidding behavior in the primary auction is examined. The auctioneer’s expected revenues from organizing the primary market as a discriminatory auction versus a uniform-price auction are compared, and sufficient conditions under which the uniform-price auction will yield higher expected revenues are obtained. An example of our model, with the primary market organized as a discriminatory auction, is the U.S. Treasury bill market.